Zirconium Carbide Mediates Coke‐Resistant Methane Dry Reforming on Nickel‐Zirconium Catalysts. Issue 50 (15th November 2022) - Haug, Leander; Thurner, Christoph; Bekheet, Maged F.; Bischoff, Benjamin; Gurlo, Aleksander; Kunz, Martin; Sartory, Bernhard; Penner, Simon; Klötzer, Bernhard
Abstract: Graphitic deposits anti‐segregate into Ni 0 nanoparticles to provide restored CH4 adsorption sites and near‐surface/dissolved C atoms, which migrate to the Ni 0 /ZrO2 interface and induce local Zr x C y formation. The resulting oxygen‐deficient carbidic phase boundary sites assist in the kinetically enhanced CO2 activation toward CO(g). This interface carbide mechanism allows for enhanced spillover of carbon to the ZrO2 support, and represents an alternative catalyst regeneration pathway with respect to the reverse oxygen spillover on Ni‐CeZr x O y catalysts. It is therefore rather likely on supports with limited oxygen storage/exchange kinetics but significant carbothermal reducibility. Abstract : Zr‐Carbide promoted Methane Dry Reforming on Ni x Zr y : Graphitic deposits anti‐segregate into Ni 0 nanoparticles to provide restored CH4 adsorption sites and near‐surface/dissolved C atoms, which migrate toward the Ni 0 /ZrO2 interface and induce local Zr x C y formation. The resulting oxygen‐deficient carbidic phase boundary sites assist in kinetically enhanced CO2 activation toward CO(g).